Therapeutic Effect of Epidermal Growth Factor Combined With Nano Silver Dressing on Diabetic Foot Patients - Zhang, Kaihua; Li, Yiran; He, Jiarui; Xu, Jiasheng; Wan, Yanhua; Wan, Shasha; Wang, Riwei; Zeng, Qingfu (Frontiers in Pharmacology, 2021)
Objective: To investigate the clinical efficacy of epidermal growth factor combined with nano silver dressing in the treatment of diabetic foot wounds. Methods: A total of 160 patients with diabetic foot ulcers admitted to the Second Affiliated Hospital of Nanchang University from 2015-06 to 2018-06 were selected to participate in the experiment. A randomized table method was used to randomly divide 160 patients into 4 groups: 40 in the epidermal growth factor group, 40 in the nano-silver dressing group, 40 in the combined group, and 40 in the saline control group (normal saline). Each group was given a dressing change every other day, and the time required for wound healing to each healing stage was observed. The healing rate of the wound surface and the growth degree of granulation tissue were graded in the healing stage.After 8 weeks of treatment, the wound exudate was cultured in bacteria. Results: There was no significant difference in the time between the four groups of patients reaching the effective phase of treatment (level 1).Compared with the control group, the epidermal growth factor group and the combined group achieved shorter wound healing time 2 and 3, and the difference was significant (p<0.05); and the combined group had shorter wound repair time than the epidermal growth factor group (p<0.05). The wound repair time of the nano-silver dressing group was shorter than that of the control group, but the difference was not significant (p>0.05). Conclusion: There is no significant difference in wound healing between the four groups during the clinically effective period. After this period, combined use of recombinant epidermis Growth factors and nano-silver dressings have a significant effect on promoting wound healing and can effectively prevent infection.